Parameter estimation of a tumor growth model using the real-valued genetic algorithm - Agrawal, Tanuja; Agrawal, Vinti (Global Journal of Mathematical Analysis, 2014)
This paper presents the use of real-valued Genetic Algorithm (GA) to evolve set of unknown parameters and initial conditions for tumor growth model using data extracted from El-Gohary [1]. The main focus of this work is to reach beyond the possibilities of traditional optimization methods in obtaining the far situated global optimum solutions with the help of arithmetic crossover and uniform mutation operators. Experimental results show the effectiveness of our approach by comparing the results obtained against the one mentioned in El-Gohary [1]. Keywords: Real-Valued Genetic Algorithms; Tumor Growth Model; Parameter Estimation.